College Begins in Kindergarten: A Path to Higher Education Through Family-School Partnerships in a K-5 School - Morgan, K. Kayon (Central European Journal of Educational Research, 2023)
As income inequality rises in the United States, students from low-income backgrounds and other excluded identities are likelier to remain in the lower income percentile, especially if they do not have college degrees (Kochhar & Cilluffo, 2018). Therefore, a critical approach is to focus on what happens before middle and high school, realizing that early childhood is prime for students to learn about college and their future. This study explored the practices influencing college-going aspirations for marginalized students in a K-5 school that engages teachers and families. The exploration extends the literature on how schools prepare elementary-aged students to develop college-going aspirations. The case study design collected data from observations, an administrative interview, and a document review. Findings revealed social and environmental practices influencing students and families regarding college-going attitudes and aspirations. The results have implications for curriculum and school culture to redefine the postsecondary conversation.